Dabigatran and the Risk of Staphylococcus aureus Bacteremia: A Nationwide Cohort Study. (1st June 2020) - Butt, Jawad H; Fosbøl, Emil L; Verhamme, Peter; Gerds, Thomas A; Iversen, Kasper; Bundgaard, Henning; Bruun, Niels Eske; Larsen, Anders R; Petersen, Andreas; Andersen, Paal S; Skov, Robert L; Gislason, Gunnar H; et al.
Abstract: Background: Treatment with dabigatran, an oral direct thrombin inhibitor, reduces the virulence of Staphylococcus aureus in in vitro and in vivo models. However, it remains to be determined whether dabigatran reduces the risk of S. aureus infections in humans. We investigated the incidence rate of S. aureus bacteremia (SAB) in patients with atrial fibrillation treated with the direct thrombin inhibitor dabigatran compared with patients treated with the factor Xa-inhibitors rivaroxaban, apixaban, and edoxaban. Methods: In this observational cohort study, 112 537 patients with atrial fibrillation who initiated treatment with direct oral anticoagulants (August 2011–December 2017) were identified from Danish nationwide registries. The incidence rates of SAB in patients treated with dabigatran versus patients treated with the factor Xa-inhibitors were examined by multivariable Cox regression accounting for time-dynamic changes in exposure status during follow-up. Results: A total of 112 537 patients were included. During a median follow-up of 2.0 years, 186 patients in the dabigatran group and 356 patients in the factor Xa-inhibitor group were admitted with SAB. The crude incidence rate of SAB was lower in the dabigatran group compared with the factor Xa-inhibitor group (22.8 [95% confidence interval [CI], 19.7–26.3] and 33.8 [95% CI, 30.5–37.6] events per 10 000 person-years, respectively). In adjusted analyses, dabigatran was associated with a significantly lower incidence rate of SAB compared with factor Xa-inhibitors (incidence rate ratio, .76; 95% CI, .63–.93). Conclusions: Treatment with dabigatran was associated with a significantly lower incidence rate of SAB compared with treatment with factor Xa-inhibitors. Abstract : Treatment with dabigatran, compared with rivaroxaban and apixaban, was associated with a significantly lower incidence rate of Staphylococcus aureus bacteremia (SAB). This finding may have important implications for evolvement of prevention and treatment strategies for SAB and warrants further investigation.